Patient and Health-Care Provider Interpretation of do not Resuscitate and do not Intubate - Pirinea, Heather (Indian J Palliat Care, 2016)
BACKGROUND: Advance directives and end of life care are difficult discussions for both patients and health-care providers (HCPs). A HCP requires an accurate understanding of advanced directives to educate patients and their family members to allow them to make an appropriate decision. Misinterpretations of the do not resuscitate (DNR), do not intubate (DNI), and the Physicians Orders for Life-Sustaining Treatment (POLST) form result in ineffective communication and confusion between patients, family members, and HCPs. METHODOLOGY: An anonymous, multiple choice online and paper survey was distributed to patients, family members of patients (PFMs), and HCPs from December 12, 2012 to March 6, 2013. Data regarding demographics, the accuracy of determining the correct definition of DNR and DNI, the familiarity of the POLST form and if a primary care physician had discussed advanced directives with the participants were collected. RESULTS: A total of 687 respondents participated in the survey. Patients and PFMs could not distinguish the definition of DNR (95% confidence interval [CI] [1.453–2.804]) or DNI (95% CI (1.216–2.334)) 52% of the time while HCPs 35% and 39% of the time (P < 0.0005). Regarding the POLST form, 86% of patients and PFMs and 50% of HCPs were not familiar with the POLST form. Sixty-nine percent of patients and family members reported that their primary care physician had not discussed advance directives with them. Twenty-four percent of patients and family members reported that they had previous health-care experience and this was associated with increased knowledge of the POLST form (P < 0.0005). An association was also seen between the type of HCP taking the survey and the ability to correctly identify the correct definition of DNR (P < 0.0005). CONCLUSION: Discussion of end of life care is difficult for patients and their family members. Often times multiple discussions are required in order to effectively communicate the definition of DNR, DNI, and the POLST form. Education of patients, family members, and HCPs is required to bridge the knowledge gap of advance directives.